Pengaruh Strategi KWL (Know-Want to Know-Learned) Terhadap Keterampilan Membaca Pemahaman Siswa Kelas IV SDN Cipayung 01 Tangerang Selatan - Fauzyah, Rahma Tri (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
A teacher needs to have good skills to develop their students' reading comprehension skills. In this case, the selection of and use of appropriate learning strategies is certainly one of the things that must be considered. The purpose of this study was to determine the significance of the effect of the KWL (Know-Want to Know-Learned) strategy on the reading comprehension skills of grade IV students at SDN Cipayung 01 South Tangerang. The research method used is an experimental method, namely a quasi experimental design. The research instrument was a reading comprehension skill test in the form of a project assessment consisting of 10 valid and reliable questions. From the reading comprehension skill test scores, it was determined that both classes were normally distributed and homogeneous. Then, according to the results of the data analysis obtained the average value of the experimental class taught using the KWL (Know-Want to Know-Learned) strategy is 79,89, while the average value of the control class taught using the expository strategy is 56,88. With the results of the hypothesis test using the t-test obtained a Sig. (2-tailed) of 0,000, with 0,000 < 0,05, then H0 is rejected and H1 is accepted. This shows that there is a significant effect of the KWL (Know-Want to Know-Learned) strategy on the reading comprehension skills of grade IV students at SDN Cipayung 01 South Tangerang, with a significance value of 0,000. The use of the KWL (Know-Want to Know-Learned) strategy is expected to be used as an innovation or alternative for teachers in implementing learning strategies that can help students train and develop reading comprehension skills.